Implementasi Word Of Mouth Marketing di Era Digital Pada PT. ZUZU Teknologi Servis (Zuzu Hospitality) - Mahdy Alief Setiawan (JIMSI: Jurnal Ilmiah Mahasiswa Ilmu Komunikasi, 2023)
Zuzu Hospitality is a Software as a Service (SaaS) service that helps hotel owners manage operations, market rooms on various Online Travel Agent (OTA) sites, and manage income. The research entitled